Diagnostic and prognostic role of cardiac magnetic resonance in patients with MINOCA. (3rd October 2022) - Mileva, N; Paolisso, P; Gallinoro, E; Bergamaschi, L; Pizzi, C; Barbato, E; Penicka, M; Andreini, D; Vassilev, D I
Abstract: Background: Myocardial infarction with non-obstructed coronary arteries (MINOCA) is common in current clinical practice and cardiac magnetic resonance (CMR) plays an important role in the present management of this group of patients. However, there are still a lot of controversies concerning the etiology behind the syndrome of MINOCA. Furthermore, the prognostic value of CMR in patients with MINOCA is still undetermined. Purpose: We aimed to determine the diagnostic and prognostic value of CMR in the management of patients with MINOCA. Methods: A systematic review was performed to identify studies reporting the results of CMR findings in MINOCA patients (non-obstructive CAD or normal coronary arteries). Random effects models were used to determine the prevalence of different disease entities – myocarditis, myocardial infarction, Takotsubo cardiomyopathy or normal CMR findings. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to evaluate the prognostic value of CMR diagnosis in the subgroup of studies that reported clinical outcomes. Major adverse clinical events (MACE) were defined based on the specific study definitions and included cardiovascular death, non-fatal myocardial infarction, and cardiovascular hospitalization. Results: 31 studies comprising 4119 patients were included. Mean age was 54.1±3.3, 59% were males. The pooled prevalence of myocarditis was 32% (95% CI 0.25 to 0.39), myocardial infarction (MI) - 21% (95% CI 0.17 to 0.24), Takotsubo cardiomyopathy −12% (95% CI 0.09 to 0.16). Normal findings were found in 23% (95% CI 0.14 to 0.35), figure 1. In a subgroup analysis of seven studies (900 patients) that reported clinical outcomes the prognostic value of the CMR was assessed. CMR diagnosis of myocarditis was not significantly associated with increased risk of MACE (pooled OR, 1.50; 95% CI, 0.46 to 4.87; p=0.459). However, both diagnosis of MI and Takotsubo were significantly associated with increased risk of combined clinical outcomes (pooled OR, 1.75; 95% CI, 1.12 to 3.59; p<0.05 and pooled OR, 2.19; 95% CI, 1.34 to 5.27; p<0.001). Conclusion: In patients with MINOCA CMR brings important diagnostic and prognostic role. The pooled prevalence of myocarditis was 32%, of MI – 21% and of Takotsubo – 12%. The CMR diagnosis of MI and Takotsubo was associated with increased risk of MACE. Funding Acknowledgement: Type of funding sources: None.